2018
DOI: 10.1111/psyp.13301
|View full text |Cite
|
Sign up to set email alerts
|

Hypomania and depression associated with distinct neural activity for immediate and future rewards

Abstract: Bipolar spectrum and unipolar depressive disorders have been associated with distinct and opposite profiles of reward‐related neural activity. These opposite profiles may reflect a differential preexisting vulnerability for both types of disorders. In support, recent ERP studies find that, following reward feedback, a larger reward positivity (RewP) is associated with greater vulnerability for bipolar spectrum disorders, whereas a smaller RewP is associated with greater vulnerability for depression. However, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…The ANOVA yielded… an interaction with Group (F(1,74) = 6.08, p < .05, ηp2 = .08). 55 Glazer et al (2019) First, following immediate outcomes, we predicted that proneness to hypomania and depressive tendencies would be related to an elevated and blunted RewP, respectively, consistent with prior studies.…”
Section: Attenuated Interactionsupporting
confidence: 78%
“…The ANOVA yielded… an interaction with Group (F(1,74) = 6.08, p < .05, ηp2 = .08). 55 Glazer et al (2019) First, following immediate outcomes, we predicted that proneness to hypomania and depressive tendencies would be related to an elevated and blunted RewP, respectively, consistent with prior studies.…”
Section: Attenuated Interactionsupporting
confidence: 78%
“…The LPP follows the RewP in time, capturing later-stage outcome processing in reward tasks (30), and may reflect more downstream processing of output from the earlier evaluation systems (31). The LPP has frequently been examined using emotionpicture viewing tasks (28,(32)(33)(34), though more recent studies demonstrated the LPP's role in reward processing in healthy controls (HC) (35)(36)(37)(38)(39) and motivated attention to potential rewards or punishments in SZ (40). Blunted LPP following reward gains has also been associated with higher negative symptoms in a transdiagnostic sample that included schizophrenia-spectrum disorders (41).…”
Section: Introductionmentioning
confidence: 99%
“…A smaller RewP is linked to major depression (Belden et al, 2016;Bress et al, 2013;Liu et al, 2014;Nelson et al, 2016), more severe depressive symptoms (Bress et al, 2012;Foti & Hajcak, 2009), and substance use disorders (Joyner et al, 2019). In contrast, the RewP is enhanced in hypomania (Glazer et al, 2019;Mason, O'Sullivan, Blackburn, et al, 2012). Studies suggest that the RewP is source-localized to the striatum (Carlson et al, 2011;Foti et al, 2011) and reflects phasic increases in dopamine signaling in the frontostriatal reward circuit .…”
Section: The Reward Positivity (Rewp)mentioning
confidence: 99%